Allelopathic effects of pathogenic fungi on weed plants of soybean and corn crops - Ariane Spiassi; Lúcia Helena Pereira Nóbrega; Danielle Medina Rosa; Fábio Palczewski Pacheco; Jaqueline Senem; Gislaine Piccolo de Lima (Bioscience Journal, 2015)
The herbicides application can be reduced with alternative methods, as pathogenic fungi use, that produces several secondary compounds in growth medium, which has phytotoxicity. Thus, the aim of this study was to determine the allelopathic activity of culture filtrate produced by pathogenic fungi: Fusarium solani, Macrophomina phaseolina Fusarium graminearum and Diplodia maydis, on germination and development of horseweed (Conyza canadensis), hairy beggarticks (Bidens pilosa) and wild poinsettia (Euphorbia heterophylla). This effect was also tested on soybean and corn crops. The experimental design was completely randomized with twenty treatments (four filtrates of fungi culture, with 0, 5, 10, 15 e 20% concentrations) and four replications. Data were submitted to analysis of variance and regression. The results indicated that filtered of Fusarium solani culture presented a negative effect on horseweed, hairy beggarticks and wild poinsettia without affecting negatively soybeans crop. Diplodia maydis provided some reduction on horseweed and wild poinsettia growth without causing damage to maize crop.The while Macrophomina phaseolina filtrate decreased a seedlings growth of wild poinsettia without affecting negatively corn. This suggests filtrates can be used to control weeds in a sustainable ecological way as well as an alternative to reduce herbicides application, thus, protecting the environment.